Original decoloniality, mestizo baroque and territory in Latin America (from the Rosario of Puebla to Santa María Tonantzintla of Cholula, México) - DA COSTA, Everaldo Batista; Tirapeli, Percival [UNESP]; Moncada, José Omar (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
The artistic, architectural and historical importance of the Rosario Chapel (Puebla) and the Church of Santa María Tonantzintla (Cholula), in Mexico, considering the small number of studies that relate these temples, makes it a challenge to analyze them simultaneously. Therefore, the objective of this article is to identify aesthetic elements that distinguish, throughout artistic miscegenation, an original decoloniality as an indigenous praxis of re-existence in the New World, after Tonantzintla. This demands an ontological exercise on being, duration and the irruption of aesthetic praxis in the native from the colonizing process and territorial conquest. Indigenous practices, expressions, objects or strategies that demarcate objection to colonial violence are pointed out, using the mechanisms of the Conquest itself, such as the Church and the baroque style. Four fieldworks were carried out, with direct observation, production of images and a detailed description of the ornamentation of the temples. The framework intersects the history and philosophy of the Latin American baroque, decolonial theory and the aesthetic dimension of the temples decoded by its most noteworthy interpreters.
Decolonialidad originaria, barroco mestizo y territorio en América Latina (del Rosario de Puebla a Tonantzintla de Cholula, México)
Keywords: Baroque architecture; Church; Decoloniality; Indigenous; Latin America